Primary Choriocarcinoma of Colon: Case Report and Literature Review - Naoto Okazaki; Akira Tanaka; Masanori Yasuda; Yu Hiraoka; Shintaro Ishikawa; Masatoshi Yoshizawa; Hisashi Hayashi; Yoshio Gunji; Yasumitsu Hirano (Journal of the Anus, Rectum and Colon)
Primary colorectal choriocarcinoma is extremely rare with only 35 cases described in the literature during over 40 years. The neoplasm is characterized by biphasic tumor growth composed of adenocarcinomatous and choriocarcinomatous differentiation. Diagnostic elusiveness, aggressive nature and lack of established treatment make the prognosis extremely poor, and most patients die during the first year after diagnosis. We present a 66-year-old man with a primary choriocarcinoma of the transverse colon presenting with peritoneal metastasis and acute colonic obstruction. The patient was treated with systemic three-drug chemotherapy (mFOLFOXIRI: 5-fluorouracil/leucovorin + oxaliplatin + irinotecan) in combination with bevacizumab, a highly active regimen for metastatic colorectal adenocarcinoma. Tumor shrinkage was accompanied by a decrease of mononucleated trophoblast-like carcinoma cells in an endoscopic biopsy during the treatment, and the symptoms of disease were relieved within a quite short period of therapy, though rapid regrowth associated with serum beta human chorionic gonadotropin escalation occurred following discontinuation of therapy. The patient died 8 months after the initial diagnosis. Although our patient survived longer than the median survival period documented in the literature, further cases will need to be examined in the future to establish whether this antitumor treatment is effective to prolong survival.